A New Decision Making Approach for Supplier Selection: Hesitant Fuzzy Axiomatic Design - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2018)
This paper deals with the hesitancy in decision making. Since the decision makers generally doubt to evaluate the alternatives and the criteria in hesitant situations, the existing methods do not satisfy them. Therefore, hesitant versions of Fuzzy-AHP (HF-AHP) and Fuzzy omatic Design (HF-AD) are introduced in this paper. HF-AHP lets the decision makers to use hesitant fuzzy linguistic terms while performing the pairwise comparisons when they are in-decisive. HF-AD is used to define the system and design ranges of the items in a hesitant situation. In addition, a case study is revealed as a numerical example in which the best supplier is selected among six alternatives regarding five criteria. In that case study, both weighted and unweighted versions of HF-AD are used. In the weighted version, HF-AHP is used to determine the weights of the criteria. Furthermore, sensitivity analysis is performed to check the robustness of the decision. Moreover, these proposed techniques are compared with non-hesitant versions. According to the results, the decision makers feel more confident with the hesitant versions. Hence, the primary contributions of this study are to develop HF-AD and HF-AHP which are helpful for the decision makers to express their preferences in hesitant situations.
Keywords: Hesitant fuzzy axiomatic design; hesitant fuzzy AHP; supplier selection; multi-criteria decision making; sensitivity analysis; LINGUISTIC TERM SETS; CRITERIA; TOPSIS; MULTIPRODUCT; DISTANCE; MODEL; MULTIPERIOD; NETWORK; SYSTEM